Haptic-enabled teleoperation of base-excited hydraulic manipulators applied to live-line maintenance - Banthia, V.; Maddahi, Y.; Balakrishnan, S.; Sepehri, N. (Proceedings of the ... IEEE/RSJ International Conference on Intelligent Robots and Systems, 2014)
This paper investigates haptic-enabled teleoperation of a base-excited hydraulic manipulator working under a wireless communication channel. The intended application is live power line maintenance. With respect to this application, three main challenges are recognized in the field: need for the force feedback, wireless communication between master and slave sites, and base excitation of the slave manipulator. In this paper, a test rig is developed to examine how an operator's hand speed regulating scheme enhances the lineman's performance while the entire system works under a wireless communication channel and the slave base is under excitation. Two sets of experiments are performed when the haptic device produces no force and when the regulating haptic force is added to the master device. Performance of the system is evaluated by measuring four indices: operator's failure in completing a task, end-effector displacement, slave manipulator controller effort, and task completion time. Results indicate that adding the haptic force to the system helps linemen function more effectively when the system is subject to base-excitation and communicates through a wireless network.